1952
DOI: 10.1139/v52-065
|View full text |Cite
|
Sign up to set email alerts
|

The Decarboxylation of Anthranilic Acid

Abstract: Anthranilic acid is known to decarboxylate on being heated above its melting point, v r on being boiled in water. We have found that the aqueous decomposition can be acid catalyzed, but that, after the concentration of added mineral acid approximates that of the anthranilic acid, the reaction rate decreases with increasing mineral acid concentration. A mass specirometer study of the carbon dioxide produced in the decomposition has shown that C12-carboxyl anthranilic acid decomposes a t the same rate as C13-car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
3

Year Published

1961
1961
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 9 publications
1
9
0
3
Order By: Relevance
“…[4] are of the same form with respect described (3), except that the carbon dioxide produccd to [Hfl; as [H'] illcreases, the first fraction in the reaction was swept from the reaction vessel by a increases (or decreases) inoilotonically froin strcam of nitrogen gas and collecled in a liquid nitrogen kAK2 to kHAK,, and the second increases (or trap. It was then transferred to a high-vacuum line, decreases) froln lcg~l(lc~ -; k-,) to k+/(k+ sublimed 10 times from liquid nitrogen, and its volume, temperature, and pressure were measured.…”
Section: Methodsmentioning
confidence: 99%
“…[4] are of the same form with respect described (3), except that the carbon dioxide produccd to [Hfl; as [H'] illcreases, the first fraction in the reaction was swept from the reaction vessel by a increases (or decreases) inoilotonically froin strcam of nitrogen gas and collecled in a liquid nitrogen kAK2 to kHAK,, and the second increases (or trap. It was then transferred to a high-vacuum line, decreases) froln lcg~l(lc~ -; k-,) to k+/(k+ sublimed 10 times from liquid nitrogen, and its volume, temperature, and pressure were measured.…”
Section: Methodsmentioning
confidence: 99%
“…Previous investigations of anthranilic acid decarboxylation have shown that the reaction is first order in boiling aqueous solution but catalyzed by mineral acids (1,2). The aqueous-acid-catalyzed reactioil xvas coilsidered to involve attack by a proton fro111 the mineral acid on carbon 1 of the aromatic ring ( 2 ) and therefore to belong to the class of SE2 aromatic displacenle~lt reactions (3).…”
Section: Introductionmentioning
confidence: 99%
“…In the melt the reaction has been reported to be first order (2,4) but this is not very i~lfornlative since the con~position of the reaction mixture changes during the decarbosylation fro111 pure anthranilic acid to pure aniline. Since aniline could serve as proton donor it might take over the role of a second ~nolecule of anthranilic acid in an inter~nolecular reaction.…”
mentioning
confidence: 99%
See 2 more Smart Citations